Lightning Safety with a Grounded Air-Terminal: Is there a Difference between Indoor and Outdoor? - Gomes C.; Khurshid Z.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Housing; Lightning protection; Terminals (electric); Direct strike; Entertainment industry; Ground surfaces; Housing structure; Lightning safety; Potential gradients; Step potentials; Sturdy structures; Tourism industry; Working environment; Electric grounding